Traumatic Dental Injury—An Enigma for Adolescents: A Series of Case Reports - Akash Krishna; Manjunath Hampanna Malur; D. V. Swapna; Shiny Benjamin; Chris A. Deepak (Case Reports in Dentistry)
Coronal fractures of permanent dentition are the most frequent type of dental injury. Fractured anterior teeth are usually treated with conventional post and core and crown techniques, after being treated endodontically. If the original tooth fragment is retained following fracture, the natural tooth structures can be reattached using adhesive protocols. Fiber-reinforced post makes the reattachment of the crown esthetically possible with minimal preparation and reduces the possibility of tooth fracture during function. This paper presents the therapeutic approach of reattachment of crown fragment to the tooth at the cervical and middle third levels.